BRIEF CONSIDERATIONS REGARDING MEDIATION IN CRIMINAL MATTERS - LUMINITA DRAGNE (Challenges of the Knowledge Society)
Mediation is an alternative means of conflict resolution, is designed as a flexible procedure whose utility was observed in contrast to the deficiencies of the judiciary system. In the field of criminal law, mediation is part of the larger concept of the restorative justice whose aim is restoring the main victim in its rights. From this perspective, to the criminal process is intended, in principal, repairing of the victim's prejudice and, subsequently, to encourage the delinquent in taking responsibility and to acknowledge his guilt, and also to determine him to actively participate in repairing the damage caused. The ultimate goal of the process is giving back the delinquent to society and consequently, reducing the relapse. Romanian legislator has not taken this concept, and how it is regulated mediation in criminal matters is hesitant, cautious and ultimately ineffective. Specifically, in situations that will actually occur, victim-delinquent mediation will only take the form of "assisted reconciliation."